Omega and related counting polynomials of TiO2 nanostructures - Shaker, Hani; Nadeem, Imran; Imran, Muhammad (Utilitas Mathematica, 2019)
Graph Theory provides valuable mathematical tools such as counting polynomials to explore the characteristics of molecular graphs. Recently, the Omega, Sadhana and theta polynomials have been studied for the two-dimensional three-layer titania lattice and nanotube. In this paper, we formulate these polynomials for the two-dimensional six-layer titania lattice and nanotube. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.